Primary pure large cell neuroendocrine carcinoma of the urinary bladder: a case report and literature review - Sun, Zhenpeng; Liang, Xin; Zhang, Changcun; Song, Shizhang; Gao, Jiangang (Frontiers in Oncology, 2024)
Background: The large cell neuroendocrine carcinoma (LCNEC) of the urinary bladder is a rare malignancy. With its high aggressiveness and poor prognosis, the disease is often accompanied by metastasis or recurrence. The lack of specific clinical manifestations and imaging features causes considerable challenges for clinical diagnosis and treatment.Case Presentation: We report a case of LCNEC of the urinary bladder. The patient was a 79year-old male admitted to our hospital with recurrent episodes of asymptomatic gross hematuria.Based on the computed tomography (CT) scan findings, our patient presented with a bladder mass displaying invasion into the serosal layer, suggestive of muscle involvement and indicative of malignancy. The patient received a radical cystectomy, and the postoperative pathology confirmed primary, pure LCNEC of the urinary bladder. We gave him 16 cycles of toripalimab immunotherapy. As of follow-up, the patient was alive, and periodic CT reexamination showed no evidence of recurrence.We reviewed domestic and foreign literature and found no explicit treatment protocols exist for the disease. Surgical resection combined with chemotherapy were the most common treatments. Herein, we reported the first case of primary, pure LCNEC of the urinary bladder treated by radical cystectomy combined with pure immunotherapy, achieving sustained remission, which provides a new idea for the immunotherapy and integrative treatment of the disease.